Incarceration among adults living with psychosis in Indigenous populations in Cape York and the Torres Strait. (July 2021) - Charlson, Fiona; Gynther, Bruce; Obrecht, Karin; Heffernan, Ed; David, Michael; Young, Jesse T; Hunter, Ernest
Objective: The relationship between psychosis and contact with the criminal justice system for Indigenous people living in rural and remote areas is not well understood. In this study, the authors examine patterns of incarceration among Indigenous people living with psychosis in Cape York and the Torres Strait over two decades. Methods: Data were collated from a clinical database of complete psychiatric records from 1992 to 2015, extracted for all Indigenous patients with a psychotic disorder from the Remote Area Mental Health Service, and linked to the Queensland Corrections Service database. Descriptive statistics were calculated to compare characteristics between those incarcerated and those not incarcerated during the study period and to quantify patterns of incarceration including types of offences, time spent in custody and frequency of incarceration. Multivariate Cox regression analysis was used to assess associations between reported variables and 'first incarceration'. Results: Forty-five percent of Aboriginal patients ( n  = 116) were incarcerated compared with 31% of Torres Strait Islanders ( n  = 41) ( p  = 0.008), and the proportion of males incarcerated (51%, n  = 141) was approximately twice that of females (24%, n  = 35; p  = 0.001). A cluster of first incarcerations were observed in close time proximity to diagnosis of psychosis. Individuals who had a history of both alcohol and cannabis use had approximately two times higher risk of being incarcerated following positive diagnosis compared to those without a history of substance use (hazard ratio = 1.85; 95% confidence interval: [1.08, 3.17]; p  = 0.028). Males accounted for approximately 85% ( n  = 328) of sentences. The most common most serious offence was causing physical harm to others (assault – n  = 122, 31%). Conclusion: Our study found that for Aboriginal and Torres Strait Islander people with a psychotic disorder in North Queensland, criminal justice responses with resultant incarceration occurs frequently. Access to appropriate mental health services and diversion options for Indigenous Australians with psychosis should be a key public health and justice priority.